A Review of the Recent Development of Photovoltaic/Thermal (PV/T) Systems and Their Applications. Issue 1 (12th October 2020) - Garcia Noxpanco, Mayra; Wilkins, James; Riffat, Saffa
Hybrid photovoltaic/thermal systems have become an important energy technology due to their capacity of producing electrical and thermal energy simultaneously, their ease of integration into buildings and good overall performance. Conventional PV systems generate waste energy in the form of heat during the conversion of solar radiation into electricity. It has been shown that the electrical efficiency of PV panels decays with the rise in the PV cell temperature. Therefore, PV performance can be optimised if this heat is removed. Air and water are the most common media used for heat removal and the energy can then be used for heating applications in buildings. In the last five decades, researchers worldwide have carried out experimental studies, simulations and numerical modelling of different types of PV/T systems. In addition to water and air, heat removal methods such as refrigerants, PCM, heat pumps and nanofluids have been analysed. This work presents an overview and discussion of the research of the different PV/T thermal control systems of the last five years. The present study highlights key points of the different techniques that exist, such as overall efficiencies, parameters and configurations, type of system, the nature of work, country of development and applications. Based on this study, it was concluded that the PV/T systems are auspicious technology and that further work should be focused on the aesthetics of the systems to promote acceptance and improvement of the efficiency.